The prospects of antimicrobial coated medical implants. (August 2021) - Shahid, Aqsa; Aslam, Bilal; Muzammil, Saima; Aslam, Nosheen; Shahid, Muhammad; Almatroudi, Ahmad; Allemailem, Khaled S; Saqalein, Muhammad; Nisar, Muhammad Atif; Rasool, Muhammad Hidayat; Khurshid, Mohsin
The implants are increasingly being a part of modern medicine in various surgical procedures for functional or cosmetic purposes. The progressive use of implants is associated with increased infectious complications and prevention of such infections always remains precedence in the clinical settings. The preventive approaches include the systemic administration of antimicrobial agents before and after the surgical procedures as well as the local application of antibiotics. The relevant literature and existing clinical practices have highlighted the role of antimicrobial coating approaches in the prevention of implants associated infections, although the applications of these strategies are not yet standardized, and the clinical efficacy is not much clear. The adequate data from the randomized control trials is challenging because of the unavailability of a large sample size although it is compulsory in this context to assess the clinical efficacy of preemptive practices. This review compares the efficacy of preventive approaches and the prospects of antimicrobial-coated implants in preventing implant-related infections.